PENGARUH BUDAYA SEKOLAH TERHADAP KEPERCAYAAN DIRI SISWA SMP YANINDO - Azalia Niyati Hidayat; Nurmawati Nurmawati (Jurnal Ilmiah Global Education, 2023)
This study focuses on School Culture on Yanindo Middle School Students' Confidence. The objectives to be achieved from this research are: To explain the positive impact of student self-confidence in school culture, to explain that student self-confidence plays an important role in a good school culture, to find out the self-confidence of Yanindo Middle School students and to find out whether there is an influence of school culture on trust student self. The sample studied in this study consisted of 46 students, namely all Yanindo Middle School students, using the saturated sample technique as a data collection method. Data collection techniques Data collection uses questionnaires and observations with Likert scale measurements and performs descriptive analysis of variables, prerequisite analysis tests and hypothesis testing. The results of this study were obtained based on simple linear regression analysis which produced a significance value of 0.000 which, if based on the interpretation guidelines of the results, indicated that there was an effect of 52.8% in the medium category between school culture on self-confidence indicating a positive direction which if If the school culture is carried out well, the higher the student's self-confidence.